Analisis Rasio Permodalan Bmt Produsen Gema Mandiri Syariah Kota Bima - Risia, Aulia Febrina; Prana, Satrio Adi; Putri, Dina Amalya (Business Management, 2023)
This study is entitled "Capital Analysis Ratio of BMT Produsen Gema Mandiri Syariah Kota Bima" The purpose of this study is to determine the level of sharia health and compliance in the BMT  Produsen Gema Mandiri Syariah Kota Bima on aspects of capital based on cooperative classification standards according to the cooperative ministerial decree and small business and intermediate number 07 / Per / Dep.6 / IV / 2016. Analyze cooperative financial statements based on the Decree of the Minister of Cooperatives and Small and Medium Enterprises Number 07 / Per / Dep.6 / IV / 2016, Evaluate the financial performance of cooperatives. This study uses 1 type of assessment of health aspects and components in the form of: Capital. The assessment will find out how healthy BMT  Produsen Gema Mandiri Syariah Kota Bima is in terms of finance, and how obedient in predetermined sharia principles. From these calculations the BMT Produsen Gema Mandiri Syariah  was classified as "Fairly Healthy" Cooperative. This is because it has an unfavorable value because BMT  Produsen Gema Mandiri Syariah Kota Bima does not yet have a sharia supervisory board, does not yet have equity participation and financing originating from Islamic financial institutions and also cooperative management does not yet have an educational certificate for management of Islamic financial institutions issued by competent parties.